2017
DOI: 10.1186/s10397-017-1008-2
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative surgical outcome of conventional and robot-assisted total laparoscopic hysterectomy

Abstract: BackgroundTo evaluate surgical outcome in a consecutive series of patients with conventional and robot assisted total laparoscopic hysterectomy.MethodsA retrospective cohort study was performed among patients with benign and malignant indications for a laparoscopic hysterectomy. Main surgical outcomes were operation room time and skin to skin operating time, complications, conversions, rehospitalisation and reoperation, estimated blood loss and length of hospital stay.ResultsA total of 294 patients were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Our findings reveal that robotic surgery reduced the length of hospitalization by 0.90 days and any reduction in the length of hospitalization means the recovery is faster, due that an early incorporation to usual activities after the primary intervention was obtained by patients of RAH group (a difference of 1.62 days). While some authors concur on this point [17, 18, 32, 33], the biggest comparative analysis by Pasic et al [16] showed no difference in postoperative hospital stay between the robotic hysterectomy group and the CLH group.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings reveal that robotic surgery reduced the length of hospitalization by 0.90 days and any reduction in the length of hospitalization means the recovery is faster, due that an early incorporation to usual activities after the primary intervention was obtained by patients of RAH group (a difference of 1.62 days). While some authors concur on this point [17, 18, 32, 33], the biggest comparative analysis by Pasic et al [16] showed no difference in postoperative hospital stay between the robotic hysterectomy group and the CLH group.…”
Section: Discussionmentioning
confidence: 99%
“…TLH, which is associated with less complication, shorter hospital stays, and faster return to normal activities, offers a safe and feasible alternative to abdominal hysterectomy [1]. Despite the benefits, laparoscopic hysterectomy has some limitations, such as a long learning curve and requirements of high-level surgical skills [2]. Robotic surgery could overcome these difficulties, making laparoscopic surgery possible for more patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the benefits, laparoscopic hysterectomy has some limitations, such as a long learning curve and requirements of high-level surgical skills [2]. Robotic surgery could overcome these difficulties, making laparoscopic surgery possible for more patients [2]. Robotic surgery also enables surgeons to perform complex procedures more easily through improved visualization, more accurate instrument control, and easi-er use of instruments [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversion rate was lower in two large, register‐based cohort studies 16,17 . A lower estimated blood loss or a lower transfusion rate in RATLH compared with TLH has been shown in several previous observational studies, all with a study population over 1000 women 9,10,13,15,18,19 …”
Section: Discussionmentioning
confidence: 77%